The influence of childhood abuse and prenatal intimate partner violence on childbirth experiences and breastfeeding outcomes. (September 2022) - Do, Huyen Phuc; Vo, Thang Van; Murray, Linda; Baker, Philip R.A.; Murray, Aja; Valdebenito, Sara; Eisner, Manuel; Tran, Bach Xuan; Luong-Thanh, Bao-Yen; Nguyen, Lan Hoang; Dunne, Michael P.
Abstract: Background: Despite the detrimental effects and life-course health consequences of violence exposure, relatively few studies have adequate capacity to investigate the evolution of violence from childhood to motherhood. Objective: This study aims to examine the cyclical nature of childhood abuse and prenatal inter-partner violent victimization (p-IPV) and its adverse impact on childbirth trauma and exclusive breastfeeding (EBF) practice in Vietnam. Method: Using a prospective birth cohort, 150 pregnant women were recruited in the third trimester of pregnancy in Hue city in central Vietnam (Wave 1-Baseline) and re-interviewed approximately three months after delivery (Wave 2-Follow-up). The direct and indirect effects of violent victimization on subsequent childbirth experience (measured by Birth Memories and Recall Questionnaire) and EBF practice were estimated by using augmented-inverse-probability-weighted models, sensitivity analysis, and structural equation model. Results: Detrimental and prolonged effects of the inter-generational cycle of violence transverse childhood to motherhood. Women who experienced either childhood abuse or p-IPV violence were more likely to experience negative emotional childbirth memories [ARR 1.21, 95 % CI (1.04, 1.39)]. Evidence also suggested that not continuing to exclusively breastfeed at 3 months post-partum was strongly associated with prenatal depression, young age, and perceived low social status during pregnancy. Perceived strong connectedness among extended family members and social networks (i.e. nexus among family, friends, and neighborhood) provided a buffering effect by preventing EBF termination. Conclusion: This research provides insights into the protective role of social connectedness in improving breastfeeding practice. It is vital to establish wholistic antenatal care and social service system to offer specialized support and response for victims of violence and mitigate the long-term sequelae of traumatic events. Highlights: Mothers with violence victimization during childhood and during pregnancy have a higher risk of adverse childbearing experiences. Women experienced childhood abuse are more likely to suffer the harmful long-term effects on prenatal depression and being re-victimized. Prenatal depression and perceived low social status during pregnancy may predict cessation of exclusive breastfeeding postnatally. Having a strong intergenerational connectedness during pregnancy may have a buffering effect by maintaining exclusive breastfeeding.